Anti-Corruption Academic Research and Education - Krambia-Kapardis, Maria (My University, 2026)
Awarded the ACE Award, by the UN and Sheikh Tamim Bin Hamad Al Thani. It is the International Anti-Corruption Excellence Award in the Academic Research and Education category, December 2019. Kigali, Rwanda
Keywords: Education